Analysis of 340 Cases Visited Rizgary Hospital in Hawler City during 2009-2010 (Mustansiria Dental Journal, 2018)
During two years period from 2009-2010 cases with oral lesions and oral diseaseswere recorded and analyzed, based on clinical, radiographic and biopsy examinations.The oral diseases were divided into 8 groups ,including 110 cases oral lesion, otheroral diseases were trailing well behind ,followed by soft tissue swelling 51 cases,,congenital anomalies48 cases ,bone diseases 45 cases ,salivary gland diseases31,other conditions 18cases , and neuralgia 14 cases.